2021
DOI: 10.1186/s13287-021-02619-9
|View full text |Cite
|
Sign up to set email alerts
|

Single cell Raman spectroscopy to identify different stages of proliferating human hepatocytes for cell therapy

Abstract: Background Cell therapy provides hope for treatment of advanced liver failure. Proliferating human hepatocytes (ProliHHs) were derived from primary human hepatocytes (PHH) and as potential alternative for cell therapy in liver diseases. Due to the continuous decline of mature hepatic genes and increase of progenitor like genes during ProliHHs expanding, it is challenge to monitor the critical changes of the whole process. Raman microspectroscopy is a noninvasive, label free analytical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Figure shows the average spectra for each of the cell types. Identifiable peak positions are labeled and the accompanying assignments are given in Table . In cases where there is a peak label but no assignment is given, an unambiguous assignment from the existing literature could not be made. In these cases, we refrain from attempting to make an assignment.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the average spectra for each of the cell types. Identifiable peak positions are labeled and the accompanying assignments are given in Table . In cases where there is a peak label but no assignment is given, an unambiguous assignment from the existing literature could not be made. In these cases, we refrain from attempting to make an assignment.…”
Section: Resultsmentioning
confidence: 99%
“…The role of localized concentrations and biomolecular density at subcellular levels is gaining attention as a relevant phenotypic parameter for cell-type-specific functions 49 , 50 and can be indicative, for example, of the maturation state of cells and their response to xenobiotic exposures. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Proliferating human hepatocytes (ProliHHs) were induced according to previously reported methods. 17 , 34 Briefly, to generate ProliHHs at passage 1 (P1), PHHs were treated with HM for 7 days under hypoxic cell culture conditions (2% O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous investigation, we successfully performed Raman profiling of PHHs and different passages of ProliHHs and found that Raman spectroscopy could track the biochemical changes occurring during the dedifferentiation process from PHHs to ProliHHs. 34 Considering the heterogeneity of individuals and cells, we expanded the number of human donors from one to six, expanded more passages of ProliHHs, collected Raman spectra of a larger number of cells, and conducted this research to construct a more accurate and robust machine learning model for classifying PHHs and ProliHHs.…”
Section: Introductionmentioning
confidence: 99%